MODEL PEMBELAJARAN FASILITATIF UNTUK PENINGKATAN KREATIVITAS BELAJAR PROGRAM PENDIDIKAN KESETARAAN PAKET C - Hardika Hardika; Sutaryat Trisnamansyah (Jurnal Ilmiah Visi, 2010)
This research intends to develop a facilitating instructional model which can improve learning creativity in accordance with the characteristics of learning participants, learning group and principles of learning of Package C equivalency education program. The development model was applied to two learning groups of Package C equivalency education program in the City and the District of Malang with a quasi experimental design. It can be concluded that a facilitating instructional model can effectively improve learners’ learning creativity on Package C equivalency education program.